Mechanistic Studies of Hoveyda–Grubbs Metathesis Catalysts Bearing S‐, Br‐, I‐, and N‐coordinating Naphthalene Ligands. Issue 10 (12th February 2014) - Grudzień, Krzysztof; Żukowska, Karolina; Malińska, Maura; Woźniak, Krzysztof; Barbasiewicz, Michał
Abstract Derivatives of the Hoveyda–Grubbs complex bearing S‐, Br‐, I‐, and N‐coordinating naphthalene ligands were synthesized and characterized with NMR and X‐ray studies. Depending on the arrangement of the coordinating sites on the naphthalene core, the isomeric catalysts differ in activity in model metathesis reactions. In particular, complexes with the RuCH bond adjacent to the second aromatic ring of the ligand suffer from difficulties experienced on their preparation and initiation. The behavior most probably derives from steric hindrance around the double bond and repulsive intraligand interactions, which result in abnormal chemical shifts of benzylidene protons observed with 1H NMR. Furthermore EXSY studies revealed that the halogen‐chelated ruthenium complexes display an equilibrium, in which major cis‐Cl2 structures are accompanied with small amounts of isomeric forms. In general, contents of the minor forms, measured at 80 °C, correlate with the observed activity trends of the catalysts, although some exceptions complicate the mechanistic picture. We assume that for the family of halogen‐chelated metathesis catalysts the initiation mechanism starts with the cis‐Cl2⇌trans‐Cl2 isomerization, although further steps may become rate‐limiting for selected systems.